Volumetric magnetic resonance imaging study of the brain in subjects with sex chromosome aneuploidies. Issue 5 (1st May 1999) - Warwick, Michael M; Doody, Gillian A; Lawrie, Stephen M; Kestelman, Julia N; Best, Jonathan J K; Johnstone, Eve C
Abstract : OBJECTIVES: Cognitive impairment has been reported in people with sex chromosome aneuploides (SCAs) and it has been proposed that the presence of an extra sex chromosome may have an adverse effect on neurodevelopment. This study examines the hypothesis with structural MRI of the brain. METHODS: Thirty two subjects with SCA (XXX (n=12), XYY (n=10), and XXY (n=10)) from a birth cohort study were matched groupwise for age, parental social class, and height with normal controls (13 female, 26 male). Brain MRI, measurements of IQ, and a structured psychiatric interview were performed. RESULTS: The XXX females and XXY males had significantly smaller whole brain volumes than controls of the same phenotypic sex (p=0.003 and p⩽0.05 respectively). The XXY group also had bilaterally enlarged lateral ventricles (p⩽0.05). No significant differences were found between the XYY group and controls. IQ scores in all SCA groups were lower than in the control groups. CONCLUSIONS: The main result of reduced brain volumes in XXX and XXY subjects, but not in XYY subjects, indicates that the presence of a supernumerary X chromosome has a demonstrable effect on brain development.